Nanoconfined phase change materials for thermal energy applications - Aftab, Waseem; Huang, Xinyu; Wu, Wenhao; Liang, Zibin; Mahmood, Asif; Zou, Ruqiang (Energy & environmental science, 2018)
Phase change materials (PCMs) have been extensively characterized as constant temperature latent heat thermal energy storage (TES) materials. Nevertheless, the widespread utilization of PCMs is limited due to the flow of liquid PCMs during melting, phase separation, supercooling and low heat transfer rate. In order to overcome these inherent problems and to improve thermo-physical properties, the confinement of PCMs at the nanoscale has been identified as a versatile strategy, which ensures the encapsulation of PCMs in much smaller nano-containers. Such strategies including core-shell, longitudinal, interfacial and porous confinement have been widely presented in recent years to efficiently encapsulate PCMs in nanospaces and are presenting attractive ways to enhance thermal performance. This review summarizes the recent advancement and critical issues of nanoconfinement technologies of PCMs from the point of view of material design. In addition, the potential applications of nanoconfined PCMs in diverse fields, including energy conversion and storage, thermal rectification and temperature controlled drug delivery systems, are presented in detail. Finally, the major drawbacks associated with nanoconfined PCMs and their prospective solutions are also provided. This review presents a summary of recent progress and strategies in fabricating nanoencapsulated PCMs for thermal energy applications.